2017
DOI: 10.17507/tpls.0711.09
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lexical Simplification and Elaboration on Iranian Intermediate EFL Learners’ Learning and Retention of Phrasal Verbs

Abstract: Abstract-This study aimed at investigating the effect of lexical simplification and elaboration on Iranian intermediate EFL learners' learning and retention of phrasal verbs. In order to achieve this goal, a PET test was run into 130 learners. When target participants were chosen, they were assigned into three groups including two treatment groups and one control group. Through a multiple choice test, 40 out of 60 phrasal verbs were selected as target phrasal verbs. Through 8 sessions of treatment, each group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Input type, group work implementation and digital games can remarkably foster PVs acquisition among EFL learners. To clarify, Ghorbanian and Jabbarpoor (2017) compared the influence of simplified, elaborated and unmodified written input on Iranian EFL intermediate level teenagers' PVs acquisition and retrieval. Based on their study findings, it was concluded that modifying input through either simplification or elaboration facilitated PVs acquisition and recall among the study participants.…”
Section: Techniques Used To Foster Pvs Acquisitionmentioning
confidence: 99%
See 3 more Smart Citations
“…Input type, group work implementation and digital games can remarkably foster PVs acquisition among EFL learners. To clarify, Ghorbanian and Jabbarpoor (2017) compared the influence of simplified, elaborated and unmodified written input on Iranian EFL intermediate level teenagers' PVs acquisition and retrieval. Based on their study findings, it was concluded that modifying input through either simplification or elaboration facilitated PVs acquisition and recall among the study participants.…”
Section: Techniques Used To Foster Pvs Acquisitionmentioning
confidence: 99%
“…In terms of register, most PVs are frequently used in informal colloquial spoken contexts (Ghorbanian & Jabbarpoor, 2017;Rodríguez-Puente & Obaya-Cueli, 2022). Hence, they are naturally employed in native speakers' daily conversations, movies, songs, newspapers headlines and talk shows (McCarthy & O'Dell, 2007;Badri-Ahmadi & Panahandeh, 2016;Ghorbanian & Jabbarpoor, 2017;Thyab, 2019;Ton, Tran & Dang, 2023). However, some PVs are used in formal contexts (McCarthy & O'Dell, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations